Study on the Main‐Chain Structure of Amorphous Fluorine Resins for Encapsulating AlGaN‐Based DUV‐LEDs. Issue 10 (8th January 2018) - Yamada, Kiho; Nagasawa, Yosuke; Nagai, Shoko; Hirano, Akira; Ippommatsu, Masamichi; Aosaki, Ko; Honda, Yoshio; Amano, Hiroshi; Akasaki, Isamu
Abstract : The main chain structure of optically isotropic amorphous fluorine resin for encapsulating AlGaN‐based deep‐ultraviolet LEDs ( λ < 300 nm) is studied. One type of amorphous fluorine resin has a five‐membered ring with a single oxygen atom and the other has that one with two oxygen atoms. Reliability testing is performed using AlGaN‐based LEDs of 262 and 289 nm. For the resin with two oxygen atoms in the ring, visible damage to the electrode and significantly increased leakage current are considered to been caused by the photolysis of the ring induced by irradiation with deep‐ultraviolet light. In contrast, electrode damage and increased leakage are not observed in the case of the resin with the single‐oxygen ring. Abstract : The molecular structure of fluorine resins with transmittance in DUV for encapsulating DUV‐LEDs is clarified. The fluorine polymer incorporating (COCOC) rings caused the electrodes damage, resulting in device fault. The resin with the main chain of (CCCOC) terminated with CF3 ends is considered to guarantee no damage to the devices.